Ensino informatizado de frações a crianças surdas e ouvintes por meio do paradigma de equivalência de estímulos - Angelotti, Vanessa Cristina (2016)
Mathematics is viewed by many students as one of the most complex subjects and considered one of the main responsible for school failure. No one knows for sure at what time learning difficulties beginning to emerge, but among them there are the difficulties in fractions. Some studies have shown that deaf or low-hearing children have greater difficulty in understanding mathematical concepts than hearing children. The aim of this study was to investigate fraction learning in three sign language user deaf children and three hearing children, all without prior knowledge of fractions, using the computerized procedure of matching-to-sample (MTS) based on the stimulus equivalence paradigm. It was taught relations between fractions, represented as ratios of two quantities, and pictures (relations AB) and between fractions and decimal numbers (relations AC), followed by symmetry (BA and CA), transitivity (BC and CB) and generalization (the use of fractions with manipulable materials) tests. It has also been conducted a test to verify the formation of three major classes taking the decimal number (Set C) as node. The independent variable was the teaching procedure of conditional relations AB and AC and the dependent variable was the performance of children in the conditional relations. The results indicated learning of trained relations and the emergence of novel relations. All participants generalized the learned repertoire. The performances of the participants were similar, especially in the equivalence and generalization tests, allowing one to infer that deaf and hearing participants may reach the same repertoires and, sometimes, for the same repertoires, the same kind of procedure is sufficient for the two types of participants.